CaO recovered from eggshell waste as a potential adsorbent for greenhouse gas CO2. (1st November 2021) - Hsieh, Shu-Ling; Li, Fang-Yu; Lin, Pei-Ying; Beck, David E.; Kirankumar, Rajendranath; Wang, Gan-Jie; Hsieh, Shuchen
Abstract: The growing number of industrial carbon emissions have resulted in a significant increase in the greenhouse gas carbon dioxide (CO2 ), which, in turn, will have a major impact on climate change. Therefore, the reduction, storage, and reuse of CO2 is an important concern in modern society. Calcium oxide (CaO) is known to be an excellent adsorbent of CO2 in a high-temperature environment. However, since deterioration of the adsorbent is likely to occur after repeated cycles of adsorption under high temperature conditions, it would be desirable to mitigate this phenomenon, in order to maintain the stability of CaO. In the present study, common eggshell waste was used as the starting material. The main component of eggshell waste is calcium carbonate (CaCO3 ), which was purified to produce CaO. Different surfactants and amino-containing polymers were added to synthesize CaO-based adsorbents with different configurations and pore sizes. The amount of CO2 adsorbed was determined using a thermogravimetric analyzer (TGA). The results showed that the CO2 adsorption capacity of the synthetic CaO recovered from purified eggshell waste could reach 0.6 g-CO2 /g-sorbent, indicating a good adsorption capacity. CaO modified with a dopamine-containing polymer was shown to have an adsorption capacity of 0.62 g-CO2 /g-sorbent. Moreover, it showed an excellent adsorption capacity of 0.40 g-CO2 /g-sorbent, even after 10 cycles of CO2 adsorption. The present study suggests that using eggshell waste to synthesize CaO-based adsorbents for effective CO2 adsorption can not only reduce environmental waste, but also have the potential to capture greenhouse gas CO2 emissions, which conforms to the principles of green chemistry. Graphical abstract: Image 1 Highlights: CaO prepared from eggshell was applied for CO2 gas adsorption. Pore size and volume of CaO were varied by using surfactants and amino containing polymers. Through thermogravimetry analysis amount of CO2 adsorbed were analyzed. CaO prepare from dopamine containing polymer showed excellent adsorption capacity.